State Response to the COVID-19 Pandemic - Vinsensio Dugis (Scopus ID: 57201258125) (Global Strategis, 2020)
In this edition, Global Strategis specifically presents articles about the experiences of seventeen different countries from various regions in the world, on how their respective governments respond to the COVID-19 pandemic. The focus was on the first six months of 2020 as this period (January to June 2020) is considered a critical moment. It was during this period the world realizes that it is faced with a global health crisis, enforcing every  country to 'fast learning' confronting this completely new pandemic, and hence to determine the most appropriate response in confronting the difficult choice between saving people's lives or preventing the country's economic crisis. Different experiences of each country seem to suggest that above various variables affecting each of them, the initial attitude of their respective governments in assessing the deadly level of COVID-19 pandemic and the speed to act according to what is most needed are crucial factors influencing the relative success or not of the response of their respective governments. When knowing the initial information about the transmission of the virus that originated in Wuhan, China, to what extent the governments of each country see this as a force that potentially deadly outbreak? Keywords: Global Health Crisis, Pandemic Covid-19, State Response.Pada edisi ini, Global Strategis secara khusus menghadirkan tulisan tentang pengalaman tujuh belas negara dari kawasan dunia yang berbeda, bagaimana pemerintah mereka merespons pandemi COVID-19. Fokus kajian pada periode enam bulan pertama tahun 2020 karena periode ini (Januari sampai dengan Juni 2020) dianggap momen kritis. Pada periode inilah dunia mengakui mulai sedang dihadapkan pada situasi krisis kesehatan global, memaksa setiap negara ‘belajar cepat’ menghadapi pandemi yang sama sekali baru ini, untuk selanjutnya secara tepat pula menentukan respons yang paling sesuai menghadapi pilihan sulit antara menyelamatkan nyawa penduduk atau mencegah krisis ekonomi negara. Pengalaman berbeda dari berbagai negara nampaknya membawa ke suatu kesimpulan bahwa di atas kompleksitas variabel yang masing-masing memengaruhi pilihan kebijakan, nampaknya sikap awal pemerintah di dalam menilai tingkat ‘mematikan’ wabah COVID-19 serta kecepatan bertindak atas dasar kebutuhan masing-masing menjadi faktor krusial menentukan keberhasilan masing-masing negara. Ketika mengetahui informasi awal tentang adanya penularan virus yang bermula dari Wuhan, China ini, sejauh mana pemerintah masing-masing negara melihat ini sebagai kekuatan yang berpotensi sebagai wabah mematikan? Kata-kata Kunci: Krisis Kesehatan Global, Pandemi COVID-19, Respon Negara.